2017
DOI: 10.1111/evo.13361
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of hominoid cranial diversity: A quantitative genetic approach

Abstract: Hominoid cranial evolution is characterized by substantial phenotypic diversity, yet the cause of this variability has rarely been explored. Quantitative genetic techniques for investigating evolutionary processes underlying morphological divergence are dependent on the availability of good ancestral models, a problem in hominoids where the fossil record is fragmentary and poorly understood. Here, we use a maximum likelihood approach based on a Brownian motion model of evolutionary change to estimate nested hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 101 publications
(138 reference statements)
6
48
0
Order By: Relevance
“…In contrast, human skin pigmentation presents a very different pattern of among‐population variance apportionment consistent with the strong influence of natural selection in generating among‐group differences in skin color. A comparison of cranial variance apportionment in humans and common chimpanzees found that chimpanzees show much lower among‐subspecies cranial differentiation than expected under neutrality, which is consistent with relatively strong stabilizing selection acting on chimpanzees (and other hominoid taxa) …”
Section: Neutral Theorymentioning
confidence: 71%
See 1 more Smart Citation
“…In contrast, human skin pigmentation presents a very different pattern of among‐population variance apportionment consistent with the strong influence of natural selection in generating among‐group differences in skin color. A comparison of cranial variance apportionment in humans and common chimpanzees found that chimpanzees show much lower among‐subspecies cranial differentiation than expected under neutrality, which is consistent with relatively strong stabilizing selection acting on chimpanzees (and other hominoid taxa) …”
Section: Neutral Theorymentioning
confidence: 71%
“…This suggests that dissociating the human cranium into individual linear measurements may not be the most accurate means of estimating patterns of additive genetic variance relative to phenotypic variance, due to the effects of morphological integration . As noted recently by Weaver and Gunz, there is also a disconnect between the GM approach adopted by most evolutionary morphologists and the current methods for comparing directional selection gradients or detecting deviations from neutrality, which tend to be based on individual linear measurements . Hence, new methods that combine the power of GM methods for statistical shape comparison with an analytical approach based on quantitative genetic principles such as that developed by Weaver and Gunz will be important for the future development of evolutionary morphology.…”
Section: Multivariate Morphometricsmentioning
confidence: 99%
“…Since the molecular divergence of H. sapiens and the genus Pan (5–7mya) occurred at a similar time to the molecular divergence of hylobatids (5–7mya)—then the rates of morphological and genetic diversification between these two clades can be effectively compared. For example, there is evidence that cranial evolution in Homo sapiens is characterized by directional selection relative to the genus Pan , while the lineage leading to Hylobates is consistent with drift . This quantitative genetics approach, which relies on genetics together with morphology, could be extended to include hylobatid crania of all species to serve as a high‐resolution comparator for rates of hominin cranial evolution in the absence of DNA.…”
Section: Hylobatid and Hominin Evolutionary Comparisonmentioning
confidence: 99%
“…In contrast, even in recent studies for which landmark data were collected, selection gradients are commonly calculated from linear measurements (e.g., Kelly ; Schroeder et al. ; Schroeder and von Cramon‐Taubadel ), which divorces them from GM visualizations of morphology. The main exception has been the studies by Klingenberg and colleagues (Klingenberg and Leamy ; Klingenberg and Monteiro ; Klingenberg et al.…”
mentioning
confidence: 99%
“…Furthermore, existing methods for detecting deviations from neutrality (e.g., Ackermann and Cheverud ; Weaver et al. ) are not well suited to handle the large number of variables inherent to landmark data, and they often require making assumptions about parameters such as effective population sizes and split times (e.g., Schroeder and von Cramon‐Taubadel ; Weaver et al. ; Weaver and Stringer ), for which we typically have little or imprecise information.…”
mentioning
confidence: 99%